2014
DOI: 10.1371/journal.pone.0101570
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive Social Influence Increases Impulsive Choices on a Temporal Discounting Task in Young Adults

Abstract: Adolescents and young adults who affiliate with friends who engage in impulsive behavior are more likely to engage in impulsive behaviors themselves, and those who associate with prosocial (i.e. more prudent, future oriented) peers are more likely to engage in prosocial behavior. However, it is difficult to disentangle the contribution of peer influence vs. peer selection (i.e., whether individuals choose friends with similar traits) when interpreting social behaviors. In this study, we combined a novel social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 47 publications
2
43
2
Order By: Relevance
“…Our results suggest that impulsivity alone cannot explain the effects of peer presence on reaction times (also see Krajbich, Bartling, Hare, & Fehr, ). Moreover, these findings are different from the findings from studies that focused on delay discounting (Gilman et al., ; O'Brien et al., ; Weigard et al., ) which did find an increase in impulsivity in the presence of peers; therefore, future studies should examine the role of impulsivity and the facilitating versus hindering effects of peers on reaction times in more detail (for a recent discussion on impulsivity, see Steinberg & Chein, ).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Our results suggest that impulsivity alone cannot explain the effects of peer presence on reaction times (also see Krajbich, Bartling, Hare, & Fehr, ). Moreover, these findings are different from the findings from studies that focused on delay discounting (Gilman et al., ; O'Brien et al., ; Weigard et al., ) which did find an increase in impulsivity in the presence of peers; therefore, future studies should examine the role of impulsivity and the facilitating versus hindering effects of peers on reaction times in more detail (for a recent discussion on impulsivity, see Steinberg & Chein, ).…”
Section: Discussioncontrasting
confidence: 79%
“…Recent experimental studies investigating delay discounting showed that the presence of peers increased young adults' (age 18–22 years) preference for immediate rewards over larger delayed rewards (O'Brien et al., ; Weigard et al., ). Another study showed that, after viewing impulsive decisions of age‐matched peers, young adults (age 18–25 years) had a preference for smaller, earlier payments as well (Gilman, Curran, Calderon, Stoeckel, & Evins, ).…”
Section: Peer Effects: the Underlying Processmentioning
confidence: 99%
“…Peer influence on eating behavior is well-known; individuals eat more when their peers eat more, and eat less when their peers eat less [13, 14]. Peers can also effect delay discounting rates [15], as well as the willingness to expend effort to obtain rewards [16]. However, though a sizable literature exists on mechanisms of influence in the general population, and research supports the notion that social influence can spur drug use and other risky behaviors, there is a wide gap in neuroscience research focusing on substance using populations, especially cannabis users.…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been replicated in experiments manipulating group size, fear, unanimity, ethnicity, status in group, and judgment difficulty (see [ 12 ] for review). Recently we showed that in a delay-discounting task, young adults had a higher rate of impulsive choices after exposure to impulsive peer influence [ 13 ].…”
Section: Introductionmentioning
confidence: 99%